2022
DOI: 10.1038/s41591-022-01680-y
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative colitis is characterized by a plasmablast-skewed humoral response associated with disease activity

Abstract: B cells, which are critical for intestinal homeostasis, remain understudied in ulcerative colitis (UC). In this study, we recruited three cohorts of patients with UC (primary cohort, n = 145; validation cohort 1, n = 664; and validation cohort 2, n = 143) to comprehensively define the landscape of B cells during UC-associated intestinal inflammation. Using single-cell RNA sequencing, single-cell IgH gene sequencing and protein-level validation, we mapped the compositional, transcriptional and clonotypic landsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
82
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 86 publications
13
82
0
1
Order By: Relevance
“…This could be interpreted as Tph cells providing more help to B cells than Tfh cells in RA. Similar observations are reported in the inflamed colon of UC; switched memory B cells oligoclonally expand in the inflamed colon with low SHM ( 34 ). Colocalization of B cells and CXCL13-producing CD3 + T cells shown by multiple immunofluorescent stainings suggest that Tph cells provide help to switched memory B cells in UC-inflamed colitis ( 34 ).…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…This could be interpreted as Tph cells providing more help to B cells than Tfh cells in RA. Similar observations are reported in the inflamed colon of UC; switched memory B cells oligoclonally expand in the inflamed colon with low SHM ( 34 ). Colocalization of B cells and CXCL13-producing CD3 + T cells shown by multiple immunofluorescent stainings suggest that Tph cells provide help to switched memory B cells in UC-inflamed colitis ( 34 ).…”
Section: Introductionsupporting
confidence: 84%
“…DN2 cells in SLE have less SMH than other types of B cells ( 29 ). Similarly, SHM of IgG sequences from B cells of colon tissues is lower in patients with ulcerative colitis (UC) than in healthy individuals ( 34 ). These collectively indicate that human B cells differentiated at extrafollicle or peripheral tissues have less SHM than GC-B cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, our quantitative analysis showed that both area proportion and plasma cell composition of basal plasmacytosis are correlated with increasing disease severity reflected by increased NHI score. Features quantifying plasma cells in the mucosa also correlated with increasing disease severity, highlighting the role of plasma cells in UC disease biology and progression [26]. We were also able to quantify goblet cell mucin depletion, a known feature of epithelial injury in UC that has not previously been quantified [27].…”
Section: Discussionmentioning
confidence: 96%